The Influence of Self-Service Kiosks on Customers’ Revisit Intention in Fast-Food Restaurants - How, Xuan Yi; Chandrashekar, R (Research in Management of Technology and Business, 2025)
Self-service kiosks (SSKs) have revolutionized customer revisit intention, experience and service delivery in the fast-food company. In the context of Malaysian fast-food restaurants, this study investigates the influences of self-services kiosks on customer revisit intention in fast-food restaurant. Through the integration of previous literature, this study highlights the essential elements such as functionality, security, assurance, enjoyment, design, convenience, and customization that impact the revisit intention. Adopting SSK not only increases operational effectiveness but also satisfies changing customer demands for individualized and convenient experiences. The objective of conducting this study is to identify the level of customer in using self-service kiosks, and to identify the level of customer intention to revisit the fast-food restaurant. This study also aims to identify the relationship between the usage of self-service kiosks and customer intention to revisit the fast-food restaurant. The researcher has decided to conduct the survey in Malacca, Malaysia. The target population of respondents for this study is residents of Malacca. A quantitative research design was employed, and a questionnaire was established and distributed to targeted respondents. The collected data will be analysed by the Statistical Package for Social Sciences (SPSS). The results may serve as a reference to enhance the level of customer in using self-service kiosks and customer intention to revisit the fast-food restaurant.